Influencing Followership: Understanding the Perspective of Those Leading Active Discussions on Quora - Nwadiugwu, Martin C.; Nwadiugwu, Cynthia C. (Frontiers in Computer Science, 2021)
As social media influence become increasingly popular, understanding why some posts are highly followed than others, especially from the perspective of those leading the discussion allows us to gain insight on how followership is being influenced. A qualitative study of eight participants leading active discussions on Quora was conducted using semi-structured in-depth interviews, followed by thematic analysis. The open coding method was used to iteratively code related answers to develop themes. Results suggest that copyright tactics, controversial answers and sharing new information are some of the mechanisms for influencing followership. These mechanisms are built overtime through conscious strong engagement and by writing a consistently well-thought-out answer. The motivation for leading and writing answers on Quora were more intrinsic than extrinsic, and most participants believed influencing followership should not be a concern if one has the right message.